English Teacher’s Questioning Strategy in EFL Classroom Interaction - Alisa Ratna Ningsih; Dian Erlina; Rizqy Dwi Amrina (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
This study investigated the types of English teacher’s questioning strategy and Students’ perceptions towards the use of teacher questioning strategy in EFL classroom interaction. This study was conducted at SMA Muhammadiyah 1 Palembang with five students as the participants taken from the twelfthgrade nature science students by using purposeful convenience sampling. In collecting data, the researcher used one-on-one interviews through open-ended questions. The interviews conducted in the class XII IPA 1. The result of this study that those were three types of English teacher’s questioning strategy, they were (1) procedural, convergent, and (3) divergent, and the students’ perceptions toward questioning strategy, they were (1) English reading activity, (2) English speaking activity, (3) English writing activity, and (4) English listening activity. This study indicated that those were the students’ perceptions towards the types of teacher’s questioning strategy that used in EFL classroom interaction at SMA Muhammadiyah 1 Palembang.